Dynamics of zooplankton production parameters in the north-western Bering Sea in the present period - Elena. . Dulepova (Известия ТИНРО, 2016)
On the basis of plankton surveys, conducted in the north-western Bering Sea in 2010-2015, the production characteristics of zooplankton were calculated and analyzed. Zooplankton was divided into two trophic groups: predatory (mainly chaetognaths and hyperiids) and non-predatory (copepods and euphausiids) zooplankton. Considerable variations of zooplankton production parameters were observed in autumn period. This is due to the inter-annual dynamics of regional patterns of the size, taxonomic and trophic structure of zooplankton.The sharp decline in the copepod biomass after 2011 and the significant reduction in the biomass of euphausiids in 2013 were characteristic for the considered period in this region. All these features of the dynamics of copepods and euphausiids had an influence on the value of zooplankton production. The highest non-predatory zooplankton production was in 2010-2011 (up to 5081 mg/m3); the lowest, in 2012-2014 (up to 2716 mg/m3). Production of predatory zooplankton was the most significant in 2013 in the waters of the eastern part of the Gulf of Anadyr; it was associated with the presence of Themisto libellula . In general, non-predatory zooplankton in the north-western Bering Sea produced from 14.8 to 53.1 million tons during autumn; predatory zooplankton, from 5.0 to 14.2 million tons.